Tulane Engineering Is Latest Katrina Victim. - Jones, W.D (IEEE spectrum)
2007 will be the last year that Tulane University students earn degrees in computer science, electrical, mechanical, and civil engineering. The programs, say the administration, were jettisoned in the interest of keeping the rest of the New Orleans university afloat. The remaining engineering disciplines - chemical and biomedical engineering - have been subsumed into a conglomeration being called the School of Science and Engineering.